1974
DOI: 10.1084/jem.139.5.1303
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Immunological Tolerance to a Thymus-Dependent Antigen in the Absence of Thymus-Derived Cells

Abstract: Specific immunological unresponsiveness was induced using thymus-dependent antigens in congenitally athymic (nu/nu) mice, in which no T-cell function has been demonstrated. The tolerance was induced in vivo by the injection of 5–10 mg of either FGG or DNP-HGG. Spleen cells from treated mice were tested in vitro for the ability to mount thymus-independent immune responses against FGG in the presence of polymerized flagellin POL, and the DNP determinant conjugated to POL. A specific deficiency in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Unresponsiveness lacking suppressor cells has also been reported in adult animals (12)(13)(14) with the conventional DAGG tolerization protocol. The demonstration that tolerance can be induced in congenitally athymic nude mice devoid of competent T cells with both immunogenic (21) and tolerogenic (19,20) forms of heterologous gamma globulins and in adult thymectomized, X-irradiated, bone marrow-reconstituted mice (4,13) further support the postulate that tolerance can be induced in the absence of suppressor T cells. These observations coupled with the demonstration of the presence of antigen-specific-suppressor cells to HGG in primed mice (23) and the more efficient suppression of HGG-primed cells compared to normal cells (76) suggest that these suppressor cells may represent a normal regulatory mechanism operative during antigenic stimulation although their relevance to the unresponsive state to HGG must remain dubious.…”
Section: Inability Of Col Tosupporting
confidence: 49%
See 2 more Smart Citations
“…Unresponsiveness lacking suppressor cells has also been reported in adult animals (12)(13)(14) with the conventional DAGG tolerization protocol. The demonstration that tolerance can be induced in congenitally athymic nude mice devoid of competent T cells with both immunogenic (21) and tolerogenic (19,20) forms of heterologous gamma globulins and in adult thymectomized, X-irradiated, bone marrow-reconstituted mice (4,13) further support the postulate that tolerance can be induced in the absence of suppressor T cells. These observations coupled with the demonstration of the presence of antigen-specific-suppressor cells to HGG in primed mice (23) and the more efficient suppression of HGG-primed cells compared to normal cells (76) suggest that these suppressor cells may represent a normal regulatory mechanism operative during antigenic stimulation although their relevance to the unresponsive state to HGG must remain dubious.…”
Section: Inability Of Col Tosupporting
confidence: 49%
“…3). This segregation of the ability to interfere with the induction of tolerance from other mechanisms of adjuvant activity has been documented previously (71) in athymic nude mice (19,20) and in the LPS-nonresponder C3H/HeJ mouse (72), with polymerized flagellin (19), LPS (20), and lipid A-associated protein (72).…”
Section: Inability Of Col Tomentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, the mechanism is likely to differ in the case of thymus-dependent and thymus-independent antigens since the latter substances in fact nonspecifically abrogate B-cell tolerance induction by the former (7,8). Questions particularly suited to an in vitro analysis of tolerance induction in splenic B cells concern the proposal of Diener and Feldmann (9) that a multivalent presentation of antigen is an obligatory requirement for tolerance induction in the B cell, and also the kinetics of tolerance induction in a defined pool of B cells that is not being altered by the B-cell neogenesis that occurs in the bone marrow (10) .…”
mentioning
confidence: 99%
“…While it is clearly possible to induce Bcell tolerance in the absence of T lymphocytes (23)(24)(25), some workers have suggested that the presence of T cells tends to protect B lymphocytes from tolerance induction (26)(27)(28)(29)(30). In the present studies it is apparent that B-cell tolerance can be induced in reconstituted mice which were thymic deficient.…”
Section: Restoration Of a "Normal" Response To Tolerance Induction Inmentioning
confidence: 99%